2010
DOI: 10.1016/j.jjcc.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with once-daily nifedipine CR and twice-daily benidipine on prevention of symptomatic attacks in patients with coronary spastic angina pectoris—Adalat Trial vs Coniel in Tokyo against Coronary Spastic Angina (ATTACK CSA)

Abstract: Once-daily treatment with NR 40 mg was more effective than twice-daily treatment with BD in the prevention of CSA attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…It has been reported that nifedipine CR has inhibitory effects on symptomatic attacks in patients with vasospastic angina [5]. Our patient was treated with nifedipine CR for hypertension.…”
Section: Discussionmentioning
confidence: 69%
“…It has been reported that nifedipine CR has inhibitory effects on symptomatic attacks in patients with vasospastic angina [5]. Our patient was treated with nifedipine CR for hypertension.…”
Section: Discussionmentioning
confidence: 69%
“…In such cases, we follow several courses of action. First, we must consider the type of CCB, because CCBs may differ in their ability to prevent angina attacks[ 10 , 11 ]. Second, we must consider the dosing regimen, such as whether a submaximal or maximal dose or medication once or twice a day would be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if one CCB is not effective in treating VSA angina, several counter parts should be considered 18) . The following recommendations during CCB use might be helpful for refractory or intolerant cases: 1) A change or combination in the CCB type (dihydropyridine CCB and non-dihydropyridine CCB) 32,33) , 2) higher-dose CCBs than submaximal or maximal dose/once or twice a day 10) (verapamil or diltiazem 960 mg/day and/or nifedipine 100 mg/day and nitrates [34][35][36] ), 3) change from once-a-day CCB to twice a day to prevent the attacks just before the dosing time, 4) prescribing CCB at bed time to prevent attacks between midnight and early morning 14,37) , and 5) an occasional switching from generic CCBs to branded ones 38) . Nitrates…”
Section: Ccbsmentioning
confidence: 99%